Experimental study about the regulating effect of puerarin on osteoblast proliferation in vitro and related signal pathway expression - Hong-Sheng Hu (Journal of Hainan Medical University, 2017)
Objective: To study the regulating effect of puerarin on osteoblast proliferation in vitro and related signal pathway expression. Methods: Mouse osteoblasts MC353-E1 were cultured and divided into the puerarin group that were treated with 10 μg/mL puerarin and the control group that were treated with medium without drugs or serum. Before treatment as well as 12, 24 and 48 h after treatment, MTS kits were used to determine the cell proliferation activity, and enzyme-linked immunosorbent assay kits were used to determine the expression of PI3K/ AKT/FoxO signal pathway molecules and apoptosis genes. Results: 12, 24 and 48 h after treatment, the cell viability of puerarin group were significantly higher than those of control group, and p-PI3K, p-AKT, p-FoxO1 and p-FoxO3a expression were significantly higher than those of control group while Bmi, Bax, CytC, AIF and Caspase-3 expression were significantly lower than those of control group; puerarin had time-dependent regulating effect on the cell viability as well as p-PI3K, p-AKT, p-FoxO1, p-FoxO3a, Bmi, Bax, CytC, AIF and Caspase-3 expression. Conclusion: Puerarin can promote osteoblast proliferation through PI3K/AKT/ FoxO signal pathways.